Developing 21st Century Skills through Multicultural English Language Education - Destari, Dina; Anis, Nina (Yayasan Minang Darussalam, 2025)
Background. The growing diversity of classrooms and the rapid transformation of global communication demand English language education that not only develops linguistic competence but also equips learners with essential 21st-century skills. Multicultural English language education is increasingly viewed as a strategic approach to fostering critical thinking, creativity, collaboration, communication, and intercultural awareness. However, empirical evidence on how multicultural pedagogical practices contribute to these skills remains limited. Purpose. This study aimed to examine the role of multicultural English language education in developing students’ 21st-century skills. Specifically, it investigated the extent to which multicultural learning activities influence students’ critical thinking, communication, collaboration, creativity, and intercultural competence in English language classrooms. Method. A mixed-methods research design was employed involving 210 secondary and university-level students from culturally diverse educational settings. Quantitative data were collected through a validated 21st-century skills questionnaire, while qualitative data were obtained from classroom observations and semi-structured interviews. The quantitative data were analyzed using descriptive statistics and regression analysis, and the qualitative data were analyzed thematically. Results. The findings reveal that multicultural English language instruction has a significant positive effect on students’ 21st-century skills, particularly in intercultural communication, collaborative learning, and critical thinking. Students exposed to culturally responsive materials and dialogic learning activities demonstrated higher engagement and greater adaptability in diverse social interactions. Conclusion. Multicultural English language education serves as an effective pedagogical framework for integrating language learning with the development of 21st-century skills. The study underscores the importance of culturally inclusive curricula and learner-centered strategies to prepare students for global citizenship.